2-Bromo-4-chloro-6-[(E)-(2-chlorophenyl)iminomethyl]phenol - Zhang, Xinli (International Union of Crystallography, 2009)
The title compound, C(13)H(8)BrCl(2)NO, was obtained by reaction of 3-bromo-5-chlorosalicylaldehyde and 2-chlorobenzenamine in methanol. The molecule displays an E configuration with respect to the imine C=N double bond. The dihedral angle between the two benzene rings is 4.57 (11)°. The molecular conformation is stabilized by an intramolecular O—H⋯N hydrogen bond. In the crystal structure, molecules are linked by intermolecular C—H⋯O hydrogen-bonding interactions into zigzag chains running parallel to the b axis. Intermolecular Br⋯Cl [3.5289 (11) Å] and Cl⋯Cl [3.5042 (12) Å] interactions are present.